Genomic profiling of acute lymphoblastic leukemia in ataxia telangiectasia patients reveals tight link between ATM mutations and chromothripsis - Ratnaparkhe, Manasi; Jauch, Anna; Korshunov, Andrey; Milde, Till; Kunz, Joachim; Kulozik, Andreas; Jones, Barbara Christine; Pfister, Stefan (Leukemia, 2017)
Recent developments in sequencing technologies led to the discovery of a novel form of genomic instability, termed chromothripsis. This catastrophic genomic event, involved in tumorigenesis, is characterized by tens to hundreds of simultaneously acquired locally clustered rearrangements on one chromosome. We hypothesized that leukemias developing in individuals with Ataxia Telangiectasia, who are born with two mutated copies of the ATM gene, an essential guardian of genome stability, would show a higher prevalence of chromothripsis due to the associated defect in DNA double-strand break repair. Using whole-genome sequencing, fluorescence in situ hybridization and RNA sequencing, we characterized the genomic landscape of Acute Lymphoblastic Leukemia (ALL) arising in patients with Ataxia Telangiectasia. We detected a high frequency of chromothriptic events in these tumors, specifically on acrocentric chromosomes, as compared with tumors from individuals with other types of DNA repair syndromes (27 cases total, 10 with Ataxia Telangiectasia). Our data suggest that the genomic landscape of Ataxia Telangiectasia ALL is clearly distinct from that of sporadic ALL. Mechanistically, short telomeres and compromised DNA damage response in cells of Ataxia Telangiectasia patients may be linked with frequent chromothripsis. Furthermore, we show that ATM loss is associated with increased chromothripsis prevalence in additional tumor entities.